2021
DOI: 10.1158/1940-6207.capr-20-0229
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of DNA Ploidy for the Triage of HPV-Positive Chinese Women During Cervical Cancer Screening

Abstract: Running title: DNA ploidy as a triage strategy of HPV-Positive women Prevention Relevance Statement: Results from this study indicate that DNA ploidy analysis has good performance in early detection of high-grade precancerous and cancerous lesions of the cervix. This strategy could be used in the triage of HPV-positive women in cervical cancer screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…We also found that women with previous cytology results were significantly fewer than those with previous HPV results. The reason could be that DNA ploidy of cervical exfoliated cells is very prevalent in our region and is used as an alternative to cytology 26,27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that women with previous cytology results were significantly fewer than those with previous HPV results. The reason could be that DNA ploidy of cervical exfoliated cells is very prevalent in our region and is used as an alternative to cytology 26,27 …”
Section: Discussionmentioning
confidence: 99%
“…The reason could be that DNA ploidy of cervical exfoliated cells is very prevalent in our region and is used as an alternative to cytology. 26,27 Compared with the inclusion of hrHPV-positive patients in Addressing THE Need for Advanced HPV diagnostics study and 5,250 hrHPV-positive patients in IMproved Primary screening And Colposcopy Triage trial, the proportion of nonbiopsy was 8.6% (70/813) for us, 21.6% (697/3225), and 20.6% (1016/4927) for the remaining 2. The percentage of CIN2+ lesions we identified…”
mentioning
confidence: 99%
“…After Feulgen nuclei staining of the sample, the image of each nucleus was scanned and analyzed using an artificial intelligence-assisted automatic cell analyzer (LD DNA-ICM II; Landing, Wuhan, China). According to Guillaud's research, the DNA ploidy result was defined as positive based on two parameters: (1) DNA index (DI) >2.5 was considered as aneuploid, where DI represents the ratio of DNA in thyroid cancer cells/normal thyroid epithelial cells; (2) the number of aneuploid cells was not less than three in the specimen [33].…”
Section: Dna Ploidy Analysismentioning
confidence: 99%